2022
DOI: 10.3390/fluids7050149
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis for Augmentation of Thermal Performance of Single-Phase Flow in Microchannel Heat Sink of Different Sizes with or without Micro-Inserts

Abstract: With the development of miniaturized and enormous heat density generating novel technologies, the microchannel heat sink is rapidly establishing itself in modern cooling fields. Enhancement of heat transfer performance of microchannels is done by incorporating improved design structure, changing working fluids and flow conditions, using different materials for fabrication, etc. Coupling of two parameters influencing heat transfer performance of microchannels is in a nascent age, and complex coupling of heat tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It was concluded that the square wave-shaped vibration of the heat sink has a significant improvement in thermal performance than the sinusoidal wave-shaped vibration of a heat sink. Kumar and Singh [ 21 ] carried out a numerical study on different-sized microchannels with micro inserts. It was reported that microchannels with inserts effectively enhanced the heat transfer performance by 1–9%; however, these micro inserts increased the pressure drop by 14.5%.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the square wave-shaped vibration of the heat sink has a significant improvement in thermal performance than the sinusoidal wave-shaped vibration of a heat sink. Kumar and Singh [ 21 ] carried out a numerical study on different-sized microchannels with micro inserts. It was reported that microchannels with inserts effectively enhanced the heat transfer performance by 1–9%; however, these micro inserts increased the pressure drop by 14.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal performance in MCHSs of various sizes of micro-inserts were studied. Micro-inserts had the best heat transfer performance, with an improvement of 1-9% and 14.5% increase in pressure drop in the range of Reynolds numbers between 56 and 2242 [37]. In the literature, there is a lack of parametric studies on the micro-channel geometric design, especially extended surfaces having circular ribs.…”
Section: Introductionmentioning
confidence: 99%